Impact of Beauty Influencer Credibility and Emotional Attachment on Beauty Product Purchase Intention on Tiktok: The Moderating Role of Information Overload (A Case Study of TikTok Users in Denpasar, Bali) - Januba, Zia Beti; Indiani, Ni Luh Putu; Wahyuni, Ni Made (Dinasti International Journal of Management Science, 2026)
The digital marketing landscape in the beauty industry increasingly relies on the role of beauty influencers along with the rapid growth of the TikTok platform. This study aims to analyze the effect of beauty influencer credibility and emotional attachment on purchase intention for beauty products by examining the moderating role of information overload. This research employed a quantitative approach with active TikTok users in Denpasar City, Bali, as the research object. Data were collected through an online questionnaire distributed to 200 respondents selected using an accidental sampling technique. Data analysis was conducted using a variance-based structural equation modeling method. The results indicate that beauty influencer credibility and emotional attachment have a positive and significant effect on purchase intention. Furthermore, information overload was found to strengthen the influence of beauty influencer credibility and emotional attachment on purchase intention. These findings suggest that excessive information conditions encourage consumers to rely on trusted influencers when making purchasing decisions. Practically, this study recommends that the beauty industry position influencers as information guides who are able to deliver simplified, personalized, and authentic marketing messages.